Answer:
y = -1/3x -2
x-intercept = -6
Explanation:
Slope = -1/3
y-intercept = -2
Substitute values into slope intercept form ;
y =mx +b
Where ; m = slope
b =y-intercept
Equation =
![y = -(1)/(3) x -2](https://img.qammunity.org/2021/formulas/mathematics/high-school/2ryc05iweaakci70d9hwuuzvouetsxxmb0.png)
Now graph the equation
x-intercept = ?
![y = -(1)/(3) x -2](https://img.qammunity.org/2021/formulas/mathematics/high-school/2ryc05iweaakci70d9hwuuzvouetsxxmb0.png)
Arrange in standard form and Let y = 0
![y = -(1)/(3) x -2\\\\(1)/(3) x +y =-2\\\\(1)/(3) x +0=-2\\\\(1)/(3) x =-2](https://img.qammunity.org/2021/formulas/mathematics/high-school/unxmqvqxtn0t074oraibtpii4vnu6xffks.png)
Cross Multiply
![x * 1 = 3* -2\\\\x = -6\\\\=(-6,0)](https://img.qammunity.org/2021/formulas/mathematics/high-school/tsbpwvp57cvht4wvm1bdz95bxidxfi1upu.png)
So , (-6,-2)